Market power and the degree of dominance in the world palm oil market - Murniningtyas, Endah, author; Davies, Stephen P., advisor; Sampath, R. K., committee member; Ozawa, Terutomo, committee member; Dalsted, Norman L., committee member (Colorado State University. Libraries, 2000)
The thesis measures the degree of market power and trade dominance in the world palm oil market. A new empirical industrial organization model is used to estimate the degree of market power exerted by both exporting and importing countries. Two testable models are developed: i. a leader-follower model (Stackelberg), and ii. a bilateral oligopoly model. A dominance test is also introduced to measure the degree of dominance in market power exertion. The Stackelberg results indicate that both exporting and importing countries exert market power in the world palm oil market. The empirical world market price variations is closer to the triopoly solution, meaning that the exporting countries realize stronger market power in the world market. The welfare effect of these market power exertions and policy implications for exporting countries' are analyzed. This thesis contributes to the formulation of a complete framework to analyze the exertion of market power on both supply and demand sides of the market sides, which is followed by a test on the degree of dominance to measure the strength of those market power impositions.
Keywords: oil; studies; vegetable oils; plantations; soybeans; oils and fats